Magnonics: Modulation of Spin Dynamics via Voltage Control of Spin‐Lattice Coupling in Multiferroics (Adv. Funct. Mater. 10/2017). (March 2017) - Zhu, Mingmin; Zhou, Ziyao; Peng, Bin; Zhao, Shishun; Zhang, Yijun; Niu, Gang; Ren, Wei; Ye, Zuo‐Guang; Liu, Yaohua; Liu, Ming
Abstract : Magnonics is an emerging area of modern spintronics to transport and process information by spin waves, allowing for data storage and signal processing in a fast, compact, and energy‐efficient manner. In article number 1605598, Ziyao Zhou, Wei Ren, Ming Liu, and co‐workers demonstrate the modulation of spin dynamics by the spin lattice coupling effect in the multiferroic heterostructures, an achievement of great importance for energy‐efficient tunable magnonics devices.